Neural correlates of pre-performance routines in expert and novice archers - Kim, J.; Lee, H. M.; Kim, W. J.; Park, H. J.; Kim, S. W.; Moon, D. H.; Woo, M.; Tennant, L. K. (Neuroscience Letters, 2008)
The objective of the present study was to determine differences in neural networks between expert and novice archers during an archery pre-performance routine period (PPR). The experiment was conducted with eight world-class competitor or Olympic medalist archers and eight novices. In the experiment, the task was to shoot (by clicking a mouse with the right hand) if an archery target appeared on an LCD embedded in an functional magnetic resonance imaging (fMRI) scanner. The resultant fMRI data showed that when the experts were aiming, the occipital gyrus and temporal gyrus were activated, but when the novices were aiming, the frontal area was mainly activated. In addition, the anterior cingulate and posterior cingulate gyrus of the limbic lobe were also activated in the expert and novice groups, respectively. Our results demonstrated that expert and novice archers differed in levels of brain activation during the PPR period of a simulated archery task.